SMATH: Fostering an Interest in Science and Mathematics from Early Childhood through Engaging, Hands-on Learning Experiences: SMATH: Fostering an Interest in Science and Mathematics from Early Childhood through Engaging, Hands-on Learning Experiences - Ayu Lestari; Dea Santika Rahayu; Dita Aldila Krisma; Paskalia Pradanti (Pusat Penelitian dan Pengabdian Masyarakat, 2026)
Science and mathematics are fundamental disciplines that students must master, as they involve not only cognitive processes but also reasoning and problem-solving skills essential to 21st-century education. However, various studies indicate a need to increase students’ interest in these two disciplines. This community service activity aims to enhance students' interest in science and mathematics through hands-on activities conducted at two primary schools, namely MI Al Ulum Bandongan and MI Al Muta’alimin. The method applied in this activity comprises four stages: the partner problem observation stage, the preparation stage, the implementation stage, and the evaluation stage. The results of this activity show enthusiasm, participation, and a positive response from teachers and pupils towards its implementation. This response indicates a first step towards increasing interest in learning science and mathematics through hands-on activities. This activity also has the advantage of using simple tools and readily available materials, so it can be adapted by teachers and supported with systematic worksheets.